2012
DOI: 10.1155/2012/431574
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal SSRI Exposure Programs a Hypermetabolic State in Adult Mice

Abstract: Background. Selective serotonin reuptake inhibitor (SSRI) therapy complicates up to 10% of pregnancies. During therapy, SSRIs exert pleiotropic antidepressant, anorexigenic, and neurotrophic effects. Intrauterine SSRI exposure has been modeled by neonatal administration to developmentally immature rodents, and it has paradoxically elicited features of adult depression. We hypothesized neonatal SSRI exposure likewise programs a rebound hypermetabolic state in adult mice. Methods. C57BL/6 pups were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…weaning but not at adulthood (5-7 months); however, upon necropsy, both SSRI exposed female (11-12 months) and male mice (6-9 months) had reduced weight than controls [94].…”
Section: Animal Studiesmentioning
confidence: 93%
“…weaning but not at adulthood (5-7 months); however, upon necropsy, both SSRI exposed female (11-12 months) and male mice (6-9 months) had reduced weight than controls [94].…”
Section: Animal Studiesmentioning
confidence: 93%
“…2527 In addition to behavioral phenotypes consistent with rebound depression, we have shown SSRI-exposed mice have reduced left ventricular volumes and a programmed hypermetabolic state. 27,28 We further demonstrated that mice exposed to neonatal sertraline have increased adult heart rates, increased very low frequency heart rate variability, and increased urinary excretion of noradrenaline, together suggesting increased sympathetic tone. 27 Because impaired cardiac remodeling and increased sympathetic tone correlates with increased post-MI morbidity and mortality, we hypothesized that neonatal SSRI exposed mice will have increased mortality following myocardial infarction in adulthood.…”
Section: Introductionmentioning
confidence: 58%
“…The sertraline dose was chosen to reflect exposure under the assumption that maternal therapy is prescribed at the lowest effective dose (50 to 100 mg/day). 28 This dose conversion accounted for differences in body surface area, 70% oral bioavailability, and 29% placental transfer efficiency and the approximation was validated by serum sampling, as detailed in our initial publication. 28 Pups were observed daily during injections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the potential protective effect of ovarian function, bilateral ovariectomy (OVX) was completed at 4 months (control 17.7+/−2.2 wk; GR 17.6+/−2.3 wk). Post-ovariectomy data were collected an additional 4 to 6 weeks after the ovariectomies were performed (15). Analgesia during OVX included flunixin meglumine (2.5 mg/kg, subcutaneously once or twice daily for 48h with the first dose given at the time of isoflurane induction) and 0.5% bupivacaine applied to the wound margin.…”
Section: Methodsmentioning
confidence: 99%